2021
DOI: 10.1002/lt.25930
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Modifiable Predictors of Long‐Term Survival in Liver Transplant Recipients With Diabetes Mellitus Using Machine Learning

Abstract: Background: Diabetes significantly impacts long-term survival after liver transplantation (LT). We aimed to identify survival factors for diabetic LT recipients to inform preventive care, using machine learning analysis. Methods: We analyzed risk factors for mortality in patients from across the U.S. using Scientific Registry of Transplant Recipients (SRTR). Patients had undergone LT from 1987-2019, with a follow-up of 6.47 years (SD: 5.95). Findings were validated on a cohort from

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 30 publications
0
28
0
Order By: Relevance
“…This study by Yasodhara et al proves to us that long-standing diabetes mellitus increases the risk for poor outcomes more so than new-onset diabetes mellitus. (2) This makes sense. The longer one has diabetes mellitus, the more likely it is to have consequences.…”
Section: See Article On Page 536mentioning
confidence: 98%
See 2 more Smart Citations
“…This study by Yasodhara et al proves to us that long-standing diabetes mellitus increases the risk for poor outcomes more so than new-onset diabetes mellitus. (2) This makes sense. The longer one has diabetes mellitus, the more likely it is to have consequences.…”
Section: See Article On Page 536mentioning
confidence: 98%
“…There is great promise in the application of these methods to the practice of hepatology and liver transplantation, and Yasodhara et al, in this issue, aptly illustrate this. (2) Although modern practices have improved longevity following liver transplantation, morbidity and mortality owing to metabolic complications still abound. (3,4) Of liver transplantation (LT) recipients, 11% to 15% have preexisting diabetes mellitus, whereas up to 30% have diabetes mellitus after transplantation.…”
Section: See Article On Page 536mentioning
confidence: 99%
See 1 more Smart Citation
“…identified survival factors for diabetic liver transplantation recipients using ML analysis. They found that among patients with diabetes, hypertension, renal dysfunction, and use of sirolimus were top ranked features that affected survival post‐transplantation 63 …”
Section: Artificial Intelligence In Electronic Health Recordsmentioning
confidence: 99%
“…Multiple models have been proposed in recent years. Risk features for acute, postoperative outcomes, including mortality and acute kidney injury, were identified using a gradient boosting machine (13,14). Molinari et al (17) bridged traditional methods by developing a point-system for predicting 90-day mortality in liver transplant using variables identified through artificial neural networks, classification tree analysis, and logistic regression.…”
Section: Predicting Clinical Outcomes After Solid Organ Transplantation With Machine Learningmentioning
confidence: 99%